Comparative Advantage Analysis and Products Mapping of Indonesia, Malaysia, Philippines, Singapore, Thailand, and Vietnam Export Products - Jayadi, Akhmad; Aziz, Harry Azhar (Universitas Airlangga, 2017)
The research aims to answer some questions. First, what kind of export product groups that the six countries have comparative advantage? Second, is there a shifting on its comparative advantage? Third, what is the relationship between six countries? Data used in this study is secondary data which published by the World Integrated Solution (WITS) of World Bank, from 1997 to 2014. Analytical tools applied are products mapping using Revealed Symmetric Comparative Advantage (RSCA) and Trade Balance Index (TBI). The results of this study showed as follows: first, on average, the comparative advantage of six countries increase. Second, Thailand and Vietnam's comparative advantage and trade balance changes seems more dynamic than those of other four countries. Third, there is competition and complementary amongst six countries.Keywords: Comparative Advantage, Export Specialization, Products Mapping, Flying Geese JEL: P51, P33